Reconstructive Recall of Linguistic Style. Technical Report No. 286 - Brewer, William F.; Hay, Anne E.; Illinois Univ., Urbana. Center for the Study of Reading; Bolt, Beranek and Newman, Inc., Cambridge, MA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
A study investigated reconstructive recall for linguistic style. It was hypothesized that (1) features of linguistic style would be more difficult to recall than underlying content, (2) reconstructive errors would include stylistic forms recalled as standard forms when subjects lacked productive control of a particular feature of a style, and (3) reconstructive errors would include standard forms recalled as stylistic forms when subjects with productive control of a style attempted to style match. Subjects carried out recall tasks with texts of five different styles: Business, Biblical, Academic, Legal, and Primer. Objective procedures were developed to classify the style of the reconstructed responses, and the results showed that a large proportion of the total responses consisted of the predicted types of reconstructive errors. The reconstructive-style hypothesis was used to integrate a range of experimental findings from studies of memory for text. (Author/FL)
Sponsoring Agency: National Inst. of Education (ED), Washington, DC.
Contract Number: 400-76-0116.
Researchers.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Classification; Cognitive Processes; Error Analysis (Language); Higher Education; Language Processing; Linguistics; Literary Styles; Memory; Reading Comprehension; Reading Instruction; Reading Research; Recall (Psychology); Reports, Research